Why do GPs leave direct patient care and what might help to retain them? A qualitative study of GPs in South West England. Issue 1 (10th January 2018) - Sansom, Anna; Terry, Rohini; Fletcher, Emily; Salisbury, Chris; Long, Linda; Richards, Suzanne H; Aylward, Alex; Welsman, Jo; Sims, Laura; Campbell, John L; Dean, Sarah G
Abstract : Objective: To identify factors influencing general practitioners' (GPs') decisions about whether or not to remain in direct patient care in general practice and what might help to retain them in that role. Design: Qualitative, in-depth, individual interviews exploring factors related to GPs leaving, remaining in and returning to direct patient care. Setting: South West England, UK. Participants: 41 GPs: 7 retired; 8 intending to take early retirement; 11 who were on or intending to take a career break; 9 aged under 50 years who had left or were intending to leave direct patient care and 6 who were not intending to leave or to take a career break. Plus 19 stakeholders from a range of primary care-related professional organisations and roles. Results: Reasons for leaving direct patient care were complex and based on a range of job-related and individual factors. Three key themes underpinned the interviewed GPs' thinking and rationale: issues relating to their personal and professional identity and the perceived value of general practice-based care within the healthcare system; concerns regarding fear and risk, for example, in respect of medical litigation and managing administrative challenges within the context of increasingly complex care pathways and environments; and issues around choice and volition in respect of personal social, financial, domestic and professional considerations. These themes provide increased understanding of the lived experiences of working in today's National Health Service for this group of GPs. Conclusion: Future policies and strategies aimed at retaining GPs in direct patient care should clarify the role and expectations of general practice and align with GPs' perception of their own roles and identity; demonstrate to GPs that they are valued and listened to in planning delivery of the UK healthcare; target GPs' concerns regarding fear and risk, seeking to reduce these to manageable levels and give GPs viable options to support them to remain in direct patient care.